Peran Tata Usaha Dalam Pengelolaan Arsip Sekolah di Sekolah SMP Swasta Al-Jihad Medan - M Iqbal; Lucky Milan Sari; Ali Asmul; Rahmansyah Marbun (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In essence, dministration is carrying out administrative work related to writing sor collecting data, incluiding financial and other matters within a company. Archive control with planning for making, maintaning services for those who need archives, then selecting records that need to be destroyed or preserved. What is the focus of this research is the role of administration in the management of school Al-jihad Medan Middle School, Kec, Medan Tembung, Medan City, North Sumatra. As for the purpose of this study is to find out how the administrative staff in managing records. This type of research is descriptive qualitative, namely a research procedure that produces descriptive data in the form the observed people and actors, directed from the individual as a whole without isolating individuals and organizations in variables but viewing them as part of the needs. In data collecting tehniques in this study, various tehniques were used, namely interviews, observations and documentation. Based on observations made by researchers at the private junior hig school Al-jihad Medan MTs level in indrakasih,Kec, Medan Tembung, Medan City, North Sumatra, it can be seen that there are several problems, first, how to manage records that are still inefective, second, archives that are not in accordance with school year. Thirdly the arrangement of the school archives which is still not neat, as well as regarding the spatial administration which is still mixed with some honorary teachers. Fourth, inadeguate facilities and infrastructure for archive storage.